Blood-based tumor mutational burden as a biomarker in unresectable non-small cell lung cancer treated with chemoradiotherapy and durvalumab - Horndalsveen, Henrik; Haakensen, Vilde Drageset; Madebo, Tesfaye; Grønberg, Bjørn Henning; Halvorsen, Tarje Onsøien; Koivunen, Jussi; Oselin, Kersti; Cicenas, Saulius; Helbekkmo, Nina; Aanerud, Marianne; Ahvonen, Jarkko; Silvoniemi, Maria; et al. (Frontiers in Oncology, 2025)
IntroductionChemoradiotherapy followed by durvalumab is a potentially curative treatment for unresectable, locally advanced non-small cell lung cancer (NSCLC), but clinical outcomes remain highly variable. Identifying robust biomarkers is essential to refine treatment selection and enable risk-adapted strategies.MethodsIn this multicenter, prospective cohort study, 86 patients with unresectable stage III NSCLC were treated with chemoradiotherapy followed by durvalumab. Baseline plasma samples underwent genomic profiling and blood tumor mutational burden (bTMB) assessment using targeted next-generation sequencing. Associations between bTMB, circulating tumor DNA (ctDNA) alterations, PD-L1 expression, and progression-free survival (PFS) were evaluated using a one-sided significance threshold of p < 0.10.ResultsMedian PFS was 18.9 months (95% CI: 14.7–not reached), and median bTMB was 6.6 mutations/megabase. In univariable analysis, high bTMB was associated with longer PFS using both the prespecified 8.5 mut/Mb cut-off (HR: 0.65; p = 0.088) and the median 6.6 mut/Mb cut-off (HR: 0.52; p = 0.016). PD-L1 ≥ 1% was associated with longer PFS (HR: 0.38; p = 0.0003), while STK11, KEAP1, or NFE2L2 mutations in ctDNA were linked to shorter PFS (HR: 1.84; p = 0.040). In multivariable analysis, PD-L1 remained significantly associated with PFS in both models, while bTMB and STK11/KEAP1/NFE2L2 mutations were significant using the 6.6 mut/Mb cut-off.ConclusionHigh bTMB, PD-L1 expression ≥ 1%, and absence of STK11/KEAP1/NFE2L2 mutations were associated with longer PFS. These findings support integrating multiple biomarkers to improve risk stratification and personalize treatment in unresectable stage III NSCLC.Clinical Trial RegistrationThe study is registered on www.clinicaltrials.gov (ClinicalTrials.gov identifier: NCT04392505).